Geospatial Free and Open Source Software in the 21st Century Proceedings of the first Open Source Geospatial Research Symposium, OGRS 2009 - Bocher, Erwan; Neteler, Markus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book contains papers presented at the first Open Source Geospatial Research Symposium held in Nantes City, France, 8-10 July, 2009. It brings together insights and ideas in the fields of Geospatial Information and Geoinformatics. It demonstrates the scientific community dynamism related to open source and free software as well as in defining new concepts, standards or tools.
Geospatial Information and Geoinformatics -- GEOWEB and Standards -- Open Source Software Users and Developers -- Sustainable Development -- Environmental Planning and Monitoring -- Information Systems/Database/Communication Services.
Keywords: Geography; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Earth Sciences, general